ANALISIS SEMIOTIKA DALAM CERPEN IBU YANG ANAKNYA DICULIK ITU KARYA SENO GUMIRA AJIDARMA - Annisa Rahmayori; Liza Septa Wilyanti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The objective of this research was to describe the meaning contained in the short story Ibu yang Anaknya Diculik Itu by Seno Gumira Ajidarma by paying attention to the signs in the short story. The approach used is the semiotic approach of Charles Sanders Pierce. The method in this study used a qualitative descriptive method. The meaning of the sign according to Charles Sanders Pierce is the signifier (representament), object, and interpretant. Based on Pierce's concept of semiotics, the results of the study show the meaning of the signs found in the short story Ibu yang Anaknya Diculik Itu by Seno Gumira Ajidarma, which is about a mother who lost her child due to kidnapping by the authorities. Condemns the kidnappers and expresses his claim for the injustice of the fate of his son who does not know where and how he is doing. This short story reveals the socio-political criticism of the New Order regime, the many injustices experienced by the community over the political interests of the leaders. If someone whose existence is a threat to the rulers then they will do everything possible to eliminate his traces.